Masturbación en estudiantes de la unidad educativa “Amelia Gallegos Días”. Riobamba. Marzo-julio 2017. - Flores Bustos, María Soledad (2018)
This investigation is about the topic “Masturbation in Students of the Educational Unit “Amelia Gallegos Diaz” from Riobamba in March-July 2017”, because it is a very important subject considering that , through the time it is a taboo between adolescents due to masturbation has been considered as a few discussed subject with great openness by the teachers because they do not have the knowledge necessary about the masturbation to address it then be able to impart an adequate information, which has produced that adolescents get information through friends, this research was presented in order to understand the type of knowledge that have the adolescents related to this topic. The masturbation according to the dictionary of the Real Spanish mentions “it is the stimulation of the genital organs or of erogenous zones with the hand or with another means to provide sexual pleasure. This investigation was worked with a non-experimental design, the methods considered were Inductive – Deductive, the type of research was field, bibliographic and transversal and a descriptive, explanatory research level was handled. The population was 33 students. A multiple choice survey was applied. The interpretation of the results demonstrated that the students have an empirical knowledge about the masturbation whereby the students do not know the meaning of the masturbation. This influences in the normal adolescents development.